Strategi Pembinaan Rohani untuk Meningkatkan Keaktifan Pelayanan Kaum Muda di Gereja GKSI Air Upas, Kabupaten Ketapang, Provinsi Kalimantan Barat - Sumiati Titi (Lembaga Pengembangan Kinerja Dosen, 2025)
Youth ministry plays a highly strategic role in the life of the local church, particularly in addressing the challenges of the modern era marked by rapid technological advancement, shifting moral values, and the declining spiritual engagement of young generations. This community service program aims to strengthen spiritual formation that directly enhances the activeness and commitment of youth ministry in the Gereja Kristen Setia Indonesia (GKSI) Air Upas congregation. The study employs a qualitative approach through literature review and limited field observation, focusing on analyzing spiritual needs, interaction patterns, and contextual strategies for effective discipleship. The results indicate that contextual, relational, and continuous spiritual development programs significantly increase motivation, participation, and a sense of responsibility among young people in church ministry. Furthermore, the support of church leaders and the active involvement of spiritual communities are crucial in fostering a Christ-centered service mindset. This program contributes to the development of a participatory and sustainable model of youth spiritual formation that can be applied in other local churches to build a generation of young believers who are spiritually mature, active in ministry, and committed to serving Christ wholeheartedly.